Co-ligand triphenylphosphine/alkynyl-stabilized undecagold nanocluster with a capped crown structure. Issue 18 (7th April 2022) - Gao, Yan-Li; Bi, Shiqing; Wang, Yufei; Li, Jian; Su, Ting; Gao, Xuchun
Abstract : We synthesized novel co-ligand phosphine/alkynyl-stabilized Au nanoclusters with a capped crown structure, and all alkynides are exclusively in the μ1 -η 1 -end-on coordination mode which is unlike the other undecagold system. Abstract : We report the synthesis and crystal structure of novel co-ligand phosphine/alkynyl protected Au nanoclusters, with composition [Au11 (PPh3 )8 (CCPh–CF3 )2 ](SbF6 ) (1). The gold atoms in the cluster as a capped crown structure subtend C 3v symmetry with one deriving from a central icosahedron and 10 peripheral Au atoms, and all alkynides are exclusively σ coordination bonding. The mean core diameter is about 5.1 Å and the overall van der Waals diameter can be estimated to be 20.5 Å. The optical absorbance of 1 in solution reveals characteristic peaks at 384 and 426 nm and a shoulder between 450 and 550 nm.